Histochemical study of Hydatid cyst isolated from sheep within the abattoirs Kerbala province, Iraq - Obead, J. (Scientific Progress & Innovations, 2025)
Hydatid Cysts of Echinococcosis (CE) is a highly endemic parasitic zoonotic disease in Iraq that has a significant effect on the animals production (sheep, cattle, and goats) and human general health. It can affect any organ in the body, particularly the liver and lungs of the intermediate host. Carnivorous animals, notably dogs, operate as the definitive host for Echinococcus granulosus, whereas herbivorous animals, mostly sheep, are considered the intermediate host. Twenty liver samples afflicted with hydatid disease were acquired for this investigation, which employed a range of specialized stains to explore cystic echinococcosis in sheep. The samples were fixed in 10 % formalin, processed, and stained with specific stains such as masson trichrome, Periodic Acid Schiff PAS, and Alcian blue to investigate the histochemical alterations that occurred in the liver tissue. Histochemistry, After selecting parallel tissue segments from both sheep hydatid cysts, they were stained with Masson's trichrome stain for connective tissue and PAS and Alcian blue for natural or acid mucopolysaccharide. Chemical alterations in hydatid cyst-affected liver tissue offered insights into the underlying disease processes. The results of histochemical study of hydatid cyst showed positive masson's trichrome (blue color) mainly of cyst fibrous capsule, while, weak alcian blue reaction mainly of laminated layer , as well as in Periodic Acid Schiff PAS positive purple staining were recorded in both laminated layer and protoscolesis of hydatid cysts PSCs. The Conclusions of our study, According to the study's results, the ailment is zoonotic and widespread throughout Iraq. Chemical changes in hydatid cyst-affected liver tissue provide information on the underlying illness process. The histochemical study of the hydatid cyst indicated that the cyst fibrous capsule had a high masson's trichrome (blue hue), while the laminated layer had a weak alcian blue response. Both the laminated layer and PSCs had positive purple staining in PAS.